Denitrification Associated with Periphyton Communities - Triska, Frank J. (1981)
Scrapings of decomposing Cladophora sp. mats (periphyton) covering stream bed rocks produced N(2)O when incubated under N(2) plus 15% C(2)H(2). Denitrification (N(2)O formation) was enhanced by NO(3)(−) and was inhibited by autoclaving, Hg(2+), and O(2). No N(2)O was formed in the absence of C(2)H(2) (air or N(2) atmosphere). Chloramphenicol did not block N(2)O formation, indicating that the enzymes were constitutive. In field experiments, incubation of periphyton scrapings in the light inhibited denitrification because of algal photosynthetic O(2) production. The diurnal periphyton-associated denitrification rate was estimated to be 45.8 μmol of N(2)O·m(−2)·day(−1), as determined by averaging light, aerobic plus dark, and anaerobic rates over a 24-h period.